2014
DOI: 10.4304/jltr.5.6.1229-1235
|View full text |Cite
|
Sign up to set email alerts
|

Children Learning a Non-native Vowel – The Effect of a Two-day Production Training

Abstract: Abstract-The aim of this study was to investigate, how young children learn to produce a non-native vowel embedded in a pseudo-word context after short and intensive listen-and-repeat training sessions. The trained vowel contrast was chosen so that it would generate maximal learning difficulties according to models of second language learning. The group consisted of 13 7-10 year old girls. The child subjects participated in the study twice, on two consecutive days. Both days consisted of two training and two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 21 publications
1
23
1
Order By: Relevance
“…This is at odds with earlier studies using listen-and-repeat training (e.g. Jähi et al, 2015;Saloranta et al, 2015;Taimi et al, 2014) that all showed learning effects in the production of a non-native vowel quality contrast. This may, however, be simply explained by the fact that the long/short ratios for the productions of the trained stimuli were already at a high level in the baseline measurements, resulting in a ceiling effect and leaving little room for improvement.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…This is at odds with earlier studies using listen-and-repeat training (e.g. Jähi et al, 2015;Saloranta et al, 2015;Taimi et al, 2014) that all showed learning effects in the production of a non-native vowel quality contrast. This may, however, be simply explained by the fact that the long/short ratios for the productions of the trained stimuli were already at a high level in the baseline measurements, resulting in a ceiling effect and leaving little room for improvement.…”
Section: Discussioncontrasting
confidence: 60%
“…A method that is notably absent from duration training studies is production training, despite several recent studies showing it to be an effective training tool in second language acquisition. Taimi et al (2014) used listen-and-repeat training with young Finnish children in order to help them produce a Swedish vowel contrast not found in Finnish. In the study, 7-10year-old children underwent four sessions of training over two days, consisting of a total of 120 repetitions of the novel contrast, and were able to achieve more native-like production of the new vowel already after three of the four short training sessions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Tsukada et al (2005) found that Korean children learning English as an L2 learned to produce the phonetic properties of English vowels more native-like than Korean adults, when compared to age-matched native English speakers. Furthermore, it has been shown that children can benefit even from very short term production training in laboratory conditions when learning to produce a difficult L2 vowel (Taimi, Jä hi, Alku, & Peltola, 2014). This finding indicates an ability to acquire difficult vowel contrasts efficiently through simple listen and repeat training even in unnatural learning settings.…”
Section: Introductionmentioning
confidence: 67%
“…Contrary to the children tested in the present experiment, adult learners tested by Peltola et al (2020) did not benefit from auditory training of an L2 vowel contrast. In addition, the findings of Taimi et al (2014) showed that 7-10-year-old children changed their production of an L2 vowel already after three listen-and-repeat training sessions. Comparing our findings to these results further supports the proposition that children benefit rapidly and more efficiently than adults from auditory phonetic L2 training paradigms.…”
Section: Discussionmentioning
confidence: 98%